2019
DOI: 10.1080/19315260.2018.1563845
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Crude Oil on Yield and Phytochemical Composition of Selected Green Leafy Vegetables

Abstract: Total petroleum hydrocarbons (TPH) clean-up standards, intervention and/or target values, are designed to effectively manage introduction of toxic petroleum hydrocarbons into the environment. This research assessed the impact of some crude oil remediation intervention values, involving sub-lethal concentrations of crude oil, on yield and phytochemical contents of kale (Brassica oleracea L.) and lettuce (Lactuca sativa L.). Crude oil contamination within the range examined did not affect emergence; yield and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The effect on the flower production date of B. juncea is also provided in Figure 4. The influence on yield and levels of phytochemicals in the selected GLV has been previously discussed (see Odukoya et al [23]). Be that as it may, there are claims that this occurrence in plants is a result of 'petroleum auxin' identified as naphthenic acids, which (i) improve the yield of different varieties of crops; (ii) stimulates photosynthesis; and (iii) increases protein nitrogen [38].…”
Section: Effects Of Ph On the Growing Environment And Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on the flower production date of B. juncea is also provided in Figure 4. The influence on yield and levels of phytochemicals in the selected GLV has been previously discussed (see Odukoya et al [23]). Be that as it may, there are claims that this occurrence in plants is a result of 'petroleum auxin' identified as naphthenic acids, which (i) improve the yield of different varieties of crops; (ii) stimulates photosynthesis; and (iii) increases protein nitrogen [38].…”
Section: Effects Of Ph On the Growing Environment And Plantsmentioning
confidence: 99%
“…The effect on the flower production date of B. juncea is also provided in Figure 4. The influence on yield and levels of phytochemicals in the selected GLV has been previously discussed (see Odukoya et al [23]). Treatments T1, T2, T3, T4 and T5 are 0 mg/kg TPH (Control), 1500 mg/kg TPH, 3000 mg/kg TPH, 5000 mg/kg TPH, and 10,000 mg/kg TPH, respectively.…”
Section: Effects Of Ph On the Growing Environment And Plantsmentioning
confidence: 99%
“…Crude oil (petroleum) hydrocarbons are one of the most common groups of persistent organic pollutants [ 1 , 2 , 3 ]. Petroleum hydrocarbons are known to be toxic to many living organisms due to their mutagenic and carcinogenic properties [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The low rate of decomposition of oil and oil products in the environment triggers their accumulation and a gradual increase in their concentration in the environmental objects, including the soil. After getting into the soil, crude oil products destroy its structure, upset the air–water balance [ 1 ], alter the soil physicochemical properties [ 6 , 7 ], inhibit the microbial proliferation [ 1 ], disrupt the soil enzymatic activity [ 8 , 9 ], and have a negative impact on terrestrial and soil mesofauna [ 6 ], as well as on plant growth and development [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In hydrocarbon polluted environments, chlorophyll may decrease differently depending on both plant species and hydrocarbon type [18][19][20]. However, some authors have observed the inverse effect of hydrocarbons on chlorophyll content, detecting a rise at hydrocarbon concentrations of 1 g•kg −1 of hydrocarbons [20] and in soils with 10 g•kg −1 of crude oil [21].…”
Section: Hydrocarbon Impacts On Vegetationmentioning
confidence: 99%